ANALYSIS OF FACTORS INFLUENCING RESPONSIBILITY FOR VILLAGE FUND MANAGEMENT IN THE VILLAGE OF NAMORAMBE RENCY - NadiyaMeilaniTarigan; Sahala Purba (Universitas Tidar, 2022)
This research discusses the competence of Village government, Internal Control System and Financial Accessibility towards village fund management accountability, this research is very useful for monitoring the accountability of Village Fund management in Namorambe District. This research is an explanatory research with a research design of 36 villages with a sample of 93 people who found village government officials. The information used is primary in nature and analyzed using the SPSS type 23 statistical test. This type of research is quantitative. The results of this research show that the Village Government Competence has a positive and significant impact on Village Fund Management Accountability, On the other hand, the Internal Control System and Financial Report Accessibility have a negative and significant impact on Village Fund Management Accountability. On the other hand, the Village Government Competence, Internal Control System, and Financial Report Accessibility simultaneously affect and significantly affect Village Fund Management Accountability. Keywords: Village Fund Management Accountability